Pengembangan Aplikasi Edukasi Berbasis Android Sebagai Sarana Belajar Pengucapan Kosakata Bahasa Inggris - Muh. Asdar; Herman Tolle; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The use of android smartphones already part in people's lives to make ends meet. The English language is the international language that is widely used in the world today, because it's been a lot of Applications that can help learning the language of the English, but still a lot of people wrong or incorrectly pronounces the English language vocabulary, therefore designed an Application learn pronunciation of vocabulary English based android smartphone, users can learn the language of United Kingdom digitally with ease whenever and wherever. Because the purpose of Application to train pronunciation and vocabulary of the language of United Kingdom, then this proposed research on android Applications by applying voice recognition using Application programing interface (API) text to speech and speech to text. Applications created with the java Programming language, SQLite database API and google Text to speech and Speech to text. Application development using the method of prototyping because the Application is expected to match the needs of prospective users and how to learn that Application has been applied according to train pronunciation of the English language vocabulary. Testing the Application using requirement validation testing with 100% valid results, usability testing with the results of the sytem usability score is 85 which means Application feasibility and testing the accuracy of the google speech APIS with 100% accuracy with the terms of the pronunciation of the user must be clearly and not too fast.